Pengaruh Kompetensi Profesional terhadap Kinerja Guru melalui Variabel Kontrol Etos Kerja di SMK Daarul Abroor Tasikmalaya - Istinari Basori Alwi; Imam Machali (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This research aims to find out the influence between teacher professional competency variables on teacher performance controlled by work ethic variables and find out the magnitude of influence between variables. This study was located at SMK Daarul Abroor Tasikmalaya with a total sampling method that took the overall population of 40 people. The independent variable in the study was professional competence (X), while the dependent variable was teacher performance (Y). In addition, there are control variables in the form of work ethic (Z). Data collection instruments use questionnaires (questionnaires) as well as documentation. The data analysis method in this study consists of descriptive analysis and inferential analysis using statistical product and service solution (SPSS) version 22. Based on the results of the comparison between the bivariate correlation coefficient with the partial correlation coefficient obtained ryx > ryx.z = 0.807 > 0.519. From the comparison it can be concluded that professional competence can affect the performance of teachers because it is controlled by work ethic. In multiple regression analysis, there is a positive and significant influence between professional competence (X) on teacher performance (Y) through work ethic control variable (Z) with a coefficient of determination R2 of 0.706 with a significance value of 0.000 or less than α = 0.05. That is, the teacher performance variable (Y) can be explained by professional competency variable (X) and work ethic variable (Z) of 70.6%. The double regression equation is Y= 0.195X + 0.504X + 0.362X. Thus, in order for professional competence to be able to contribute to teacher performance, it must be supported by the work ethic of each individual teacher.